The good and the bad of chemokines/chemokine receptors in melanoma - Richmond, Ann (2009)
Chemokine ligand/receptor interactions affect melanoma cell growth, stimulate or inhibit angiogenesis, recruit leukocytes, promote metastasis, and alter the gene expression profile of the melanoma associated fibroblasts. Chemokine/chemokine receptor interactions can protect against tumor development/growth or can stimulate melanoma tumor progression, tumor growth and metastasis. Metastatic melanoma cells express chemokine receptors that play a major role in the specifying the organ site for metastasis, based upon receptor detection of the chemokine gradient elaborated by a specific organ/tissue. A therapeutic approach that utilizes the protective benefit of chemokines involves delivery of angiostatic chemokines or chemokines that stimulate the infiltration of cytotoxic T cells and natural killer T cells into the tumor microenvironment. An alternative approach that tackles the tumorigenic property of chemokines uses chemokine antibodies or chemokine receptor antagonists to target the growth and metastatic properties of these interactions. Based upon our current understanding of the role of chemokine-mediated inflammation in cancer, it is important that we learn to appropriately regulate the chemokine contribution to the tumorigenic `cytokine/chemokine storm', and to metastasis.